Cardiopulmonary arrest owing to oesophageal achalasia recovered completely with cardiopulmonary resuscitation followed by therapeutic hypothermia. (25th January 2013) - Hifumi, Toru; Okada, Ichiro; Inoue, Junichi; Koido, Yuichi
Abstract : We report the first case of cardiopulmonary arrest (CPA), caused by oesophageal achalasia, which recovered completely with cardiopulmonary resuscitation (CPR) followed by therapeutic hypothermia. A 53-year-old woman arrived at our hospital with recovery of spontaneous circulation (ROSC) after cardiac arrest. Dysphagia, vomiting and general fatigue had progressed for a week before. After an ambulance was called for severe dyspnoea, she collapsed in CPA. Emergency medical technicians arrived and CPR was started immediately. She experienced CPA and ROSC twice during transport to the hospital. On arrival, the patient was in respiratory distress prompting immediate intubation to eliminate airway obstruction. A CT scan revealed a transformed, occluded trachea owing to a dilated oesophagus. A large amount of food, air and saliva was suctioned with a nasogastric tube, and the patient was admitted to the intensive care unit for therapeutic hypothermia. Neurological recovery was evident. On the 11th day, pneumatic dilatation was performed and she was discharged on the 33rd day.